Peran Strategis Dakwah MUI DKI Jakarta dalam Pengembangan Masyarakat Islam - Siti Nuri Nurhaidah; Muhammad Haris Hakam; Muhammad Ridwan Yahya; Usman Umar; Hidayat Kholid (Fakultas Dakwah dan Ilmu Komunikasi, 2025)
This study analyzes the role of da'wah (Islamic outreach) of the Indonesian Ulema Council (MUI) of Jakarta under the leadership of K.H. Faiz Syukron Makmun. The study focuses on the strategic transformation undertaken, particularly related to efforts to revitalize da'wah to make it more relevant and adaptive. Using a qualitative case study method, data was collected through literature review, web news analysis, and observation. The results show a significant shift from conventional da'wah to a collaborative, inclusive model utilizing digital technology. This innovation has succeeded in increasing public participation and strengthening the MUI's image as a dynamic institution. Despite facing challenges such as liberalism, radicalism, and digital dynamics, the new leadership has demonstrated initial success in establishing the MUI as a credible reference. This study concludes that the da'wah model promoted by the MUI of Jakarta can serve as a reference for other religious institutions in facing the challenges of da'wah in the modern era.